ANALISIS PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA KARYAWAN LABORATORIUM DI PT.X - Niken Septiani Kurnia; Raden Faris Gumelar; Rifki Hidayattulloh (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
A company is built of course with a clear goal, namely to get as much profit as possible, but this is not necessarily achieved easily, there are many things that companies need to pay attention to in order to achieve these goals. One of the aspects that can affect company revenue is customer satisfaction with the products produced, where the quality of the products produced needs to be considered because this is directly proportional to customer satisfaction. To achieve customer satisfaction, many things can be done by the company, one of which is the application of Total Quality Management (TQM) as done by PT. X, where the application of TQM aims to increase competitiveness which is done by continuous improvement so that it This can affect employee performance which is also directly proportional to product quality and company earnings. This study was conducted to prove whether the implementation of TQM by PT X affects employee performance or not. The approach used in this study uses linear regression analysis, where the data used is primary data obtained from questionnaires distributed to several respondents. The results showed that variable X had an effect on variable Y with a correlation coefficient of 0.598 and the decision was made that the application of TQM had an effect on employee performance.